IGF2BP3 curbed by miR-15c-3p restores disrupted lipid storage and progesterone secretion in chicken granulosa cells under oxidative stress through AKT-Raf1-ERK1/2 signaling pathway - Zhongzhen Lin; Yanrong Gong; Chunlin Yu; Chaowu Yang; Lingqian Yin; Donghao Zhang; Yuan Tang; Feng Xu; Ye Wang; Yiping Liu (Poultry Science)
For commercial laying hens, the continuous high-intensity ovulation process leads to a significant accumulation of reactive oxygen species (ROS) in the granulosa cells, inducing oxidative stress, which accelerates ovarian aging and shortens the peak laying period. The molecular mechanisms underlying this process remain poorly understood. Therefore, we modeled the processes of oxidative stress and antioxidant in chicken granulosa cells. Small RNA sequencing revealed that miR-15c-3p expression was elevated by oxidative stress induction and attenuated by antioxidant curcumin. Functional validation with miR-15c-3p mimic and inhibitor confirmed the role of miR-15c-3p in exacerbating oxidative stress and resultant suppression of lipid droplet storage and progesterone secretion in chicken granulosa cells by targeting insulin-like growth factor 2 binding protein 3 (IGF2BP3). These regulatory effects were mediated through the sequential downstream signaling cascade of AKT-Raf1-ERK1/2. In conclusion, IGF2BP3 curbed by miR-15c-3p restores disrupted lipid storage and progesterone secretion in chicken granulosa cells under oxidative stress through AKT-Raf1-ERK1/2 signaling pathway. These findings offer new insights into the molecular mechanisms by which oxidative stress damages reproductive capacity and a theoretical basis for mitigating oxidative stress in laying hens through genetic improvement.